2005
DOI: 10.1029/2005jb003764
|View full text |Cite
|
Sign up to set email alerts
|

Anticrack inclusion model for compaction bands in sandstone

Abstract: [1] Detailed observations of compaction bands exposed in the Aztec Sandstone of southeastern Nevada indicate that these thin, tabular, bounded features of localized porosity loss initiated at pervasive grain-scale flaws, which collapsed in response to compressive tectonic loading. From many of these Griffith-type flaws, an apparently self-sustaining progression of collapse propagated outward to form bands of compacted grains a few centimeters thick and tens of meters in planar extent. These compaction bands ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 53 publications
14
138
1
1
Order By: Relevance
“…[35] In the previous studies of the mechanics of LVRSs, such as Katsman et al [2006] and Sternlof et al [2005], it was found that the significant compressive stress concentration occurs at the tip areas of the LVRSs, which rationalizes the in-plane lateral growth of the LVRSs. Our results are consistent with these results.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[35] In the previous studies of the mechanics of LVRSs, such as Katsman et al [2006] and Sternlof et al [2005], it was found that the significant compressive stress concentration occurs at the tip areas of the LVRSs, which rationalizes the in-plane lateral growth of the LVRSs. Our results are consistent with these results.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…[38] Fletcher and Pollard [1981] and Sternlof et al [2005] proposed an anticrack-inclusion model for mechanical analyses of pressure solution surfaces and compaction bands, respectively, as LVRSs using the displacement discontinuity boundary element method. Sternlof [2006] expanded this method to simulate the propagation and interaction of two elliptical anticrack bands approaching each other along parallel paths.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the occurrence of CBs typically involves localized large strains, the formulation by Gajo and Denzer [2011] was adopted, which builds upon Biot's theory providing the theoretical framework and the finite element implementation for dynamic analyses within a hyperelastic framework [Gajo, 2010] for saturated porous media with compressible constituents subjected to finite strains. The adoption of an elastic framework to model a problem involving inelastic deformation is a simplification, already adopted by other authors in similar contexts [e.g., see Sternlof et al, 2005], justified by the fact that after the onset of a CB, typically plastic deformation occurs solely within the band while the rest of the domain undergoes elastic unloading Rudnicki, 1980, Chemenda, 2009]. Further explanation of this assumption is provided by the main analysis results, discussed in section 3.…”
Section: Model Formulationmentioning
confidence: 99%